Verifying the Usefulness of Pulmonary Blood Flow Studies in the Correction of Pulmonary Atresia and Ventricular Septal Defect with Major Aortopulmonary Collateral Arteries - Zirou Huang; Fan Cao; Rongjun Zou; Minghui Zou; Weidan Chen; Wenlei Li; Guodong Huang; Li Ma; Xinxin Chen (Cardiology Research and Practice)
Objective. We retrospectively analyzed the surgical results of pulmonary blood flow studies to guide ventricular septal defect (VSD) closure in the correction of pulmonary atresia and ventricular septal defect with major aortopulmonary collateral arteries (PA/VSD/MAPCAs). Methods. A total of 57 children who were diagnosed with PA/VSD/MAPCAs and who underwent intraoperative pulmonary blood flow studies at our hospital between August 2016 and June 2019 were included. Surgery and cardiopulmonary bypass records were collected. The receiver operating characteristic (ROC) curve was used to verify the accuracy of pulmonary blood flow studies to predict VSD closure. Results. Complete VSD closure was achieved in 39 of 57 children (68.42%), with a median age of 2 years and 5 months (range: 7 months to 15 years and 9 months) and a median weight of 11.0 kg (5.7–36.5 kg). Partial VSD repair was recorded for 21 children (36.84%), including 4 children (19.05%) who underwent VSD closure in the later stages and 13 children (61.90%) who were under follow-up and waiting to undergo complete VSD closure. There was only one child (1.75%) with VSD left. After eliminating the data of four unqualified cases, the ROC curve for predicting VSD closure based on 53 pulmonary blood flow studies was obtained at a p value of <0.001, with an area under the curve of 0.922. The maximum Youden’s index was 0.713, which corresponded to an optimal mean pulmonary artery pressure cutoff value of 24.5 mmHg. Conclusion. The functional evaluation provided by pulmonary blood flow studies is highly accurate to predict intraoperative VSD repair. We recommend using pulmonary blood flow studies with a mean pulmonary artery pressure of ≤25 mmHg during blood perfusion at 3.0 L/min/m2 as the standard to repair VSD.